Modern management issues receivables in enterprises - Shakeyev, S.S.; Kassymova, А.G.; Temirbekova, L.A. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with modern receivables management system, the basic situation of the credit and cash collection enterprise policy provides practical examples of the use of credit conditions as discounts and change the loan terms. The parameters of the state of receivables, such as total sales, and the proportion of it in the implementation of the conditions of the subsequent payment, longer, reducing the requirements for assessing the reliability of the debtors and their impact. The estimation of profit necessary to compensate for the additional investment in receivables in the context of changing the term loan and changes in customer credit limits. The comparison is made possible profit from changes in credit policy to the cost of implementation of these changes. The algorithm method forfeits when dealing with customers, the credit rating of the customer account. The results of credit and cash collection enterprise policy that including decision on the quality of accounts receivable, term of the loan, providing discounts, level of collection costs, as well as reducing the risk of default. The article suggests the best option as a result of which the marginal revenue covers the marginal costs of the company, as well as the best combination of credit standards, terms of credit strategy, discounts, fines and forfeits and special conditions for customers.